Commonwealth of (In)dependent States - Dušan, Vrućinić (Social Sciences, 2018)
Following the stages from the establishment itself to the present day of the functioning of such a specific regional organization as the Commonwealth of Independent States (CIS), the article seeks to further explain the meaning of its existence, efficiency and functioning. The CIS was created in order to make the dissolution of a major world super-power, which throughout the 20th century together with the USA defined the bipolar world, as painless as possible, especially for the new countries and its nationally and ethnically diverse population. During the early years after the dissolution of the USSR, the CIS played a major role in a more flexible and less severe dissolution of the Soviet empire, alleviating the consequences for its people. A more efficient functioning among the republics in all fields was also one of the tasks of the Commonwealth, to which it was devoted to the extent which was permitted by the then, not too favourable circumstances. Difficult years of economic crisis did not allow the CIS to mutually integrate its members as much as possible on the economy level. Thanks to the economic recovery of the post-Soviet states in the early 21st century, the Commonwealth has also been transformed, reformed, and renewed, and all this in order to achieve better and more fruitful cooperation between the members. The CIS may serve as a proper example of how the former Soviet Union states are inextricably linked by social, security-political, economic, cultural, communication-transport, and other ties, thanks to the centuries-long existence of the peoples of these states in this area, despite both internal and external factors which occasionally, but temporarily halt the post-Soviet integration. Mathematically expressed, the CIS members are naturally predisposed, to be reciprocally depended on each other, just as they also have the capacity for successful cooperation in the future times and epochs brought on by the modern world.